PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAMIFIKASI BERMUATAN KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI PUISI SISWA - Fawwaz Khalifa; Bagas Kurnianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low level of students' poetry comprehension may be attributed to the limited use of engaging learning media. This study aims to develop interactive learning media based on gamification incorporating local wisdom to improve students' ability to understand poetry. The research employed a Research and Development (RnD) method using the ADDIE development model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The study involved fourth-grade students of SD Negeri Ngaliyan 05 Semarang as the research subjects. Data collection techniques included interviews, observations, documentation, written tests, and questionnaires. The data were analyzed using normality tests, T-tests, and N-gain tests. The findings showed that the interactive learning media based on gamification and infused with local wisdom were rated as "very feasible" based on expert validation, scoring 91% from media experts and 92% from content experts. The results of the T-test indicated a significant difference between the pretest and posttest scores. Teacher and student response questionnaires scored 95% and 96%, respectively, both categorized as "very feasible." The N-gain analysis showed a “moderate” category (0.68) in the small-scale trial and a “high” category (0.70) in the large-scale trial. These results indicate that gamification-based interactive media incorporating local wisdom are effective and highly feasible for improving the poetry comprehension skills of fourth-grade students at SD Negeri Ngaliyan 05 Semarang.